1993
DOI: 10.1007/bf02536235
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary α‐linolenic acid and its ratio to linoleic acid on platelet and plasma fatty acids and thrombogenesis

Abstract: The effect of dietary alpha-linolenic acid (18:3n-3) and its ratio to linoleic acid (18:2n-6) on platelet and plasma phospholipid (PL) fatty acid patterns and prostanoid production were studied in normolipidemic men. The study consisted of two 42-d phases. Each was divided into a 6-d pre-experimental period, during which a mixed fat diet was fed, and two-18 d experimental periods, during which a mixture of sunflower and olive oil [low 18:3n-3 content, high 18:2/18:3 ratio (LO-HI diet)], soybean oil (intermedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
73
4
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(90 citation statements)
references
References 34 publications
11
73
4
2
Order By: Relevance
“…Ingestion of substantially larger amounts of alpha-linolenic acid (9 g per day for 4 week) increased C20:5n-3 and C22:5n-3 in plasma triacylglycerol (by 0.3 and 0.5% of total fatty acids, respectively); however, 22:6n-3 remained unchanged (Cunnane et al, 1995). The complete lack of change in blood levels of 22:6n-3 with ingestion of alpha-linolenic acid is a consistent finding of feeding trials lasting less than several months (Chan et al, 1993;Li et al, 1999) and argues that some of the participants in our study ate more fishFa source of all three preformed long chain n-3 polyunsaturated fatsFduring the sheep diet. The combination of increased alpha-linolenic acid from the sheep-dairy products and increased fish intake could explain the fatty acid results.…”
Section: Discussionsupporting
confidence: 61%
“…Ingestion of substantially larger amounts of alpha-linolenic acid (9 g per day for 4 week) increased C20:5n-3 and C22:5n-3 in plasma triacylglycerol (by 0.3 and 0.5% of total fatty acids, respectively); however, 22:6n-3 remained unchanged (Cunnane et al, 1995). The complete lack of change in blood levels of 22:6n-3 with ingestion of alpha-linolenic acid is a consistent finding of feeding trials lasting less than several months (Chan et al, 1993;Li et al, 1999) and argues that some of the participants in our study ate more fishFa source of all three preformed long chain n-3 polyunsaturated fatsFduring the sheep diet. The combination of increased alpha-linolenic acid from the sheep-dairy products and increased fish intake could explain the fatty acid results.…”
Section: Discussionsupporting
confidence: 61%
“…Compared with the Melbourne Chinese migrants, the significantly higher proportion of platelet PL stearic acid in Ethnic difference on platelet PL fatty acid profiles D Li et al the Melbourne Caucasians may reflect those who have a high red meat intake, since red meat is the main dietary source of stearic acid in Australia (National Heart Foundation of Australia, 1994). Twenty-and 22-carbon long-chain PUFA can be either directly obtained from the diet or by in vivo biosynthesis from the parent fatty acids 18:2n-6 and 18:3n-3 by desaturation and elongation (Chan et al, 1993;Mantzioris et al, 1994). Fish and fish oil are the main sources of dietary 20-and 22-carbon omega-3 PUFA, especially high in EPA and DHA.…”
Section: Discussionmentioning
confidence: 99%
“…The n-6an-3 polyunsaturated fatty acid ratio in walnuts is roughly 5:1 (Quigley et al, 1995), whereas in canola and¯axseed oils, also advocated for their alpha linolenic acid content, the ratios are roughly 2:1 (Quigley et al, 1995) and 1:4 (Layne et al, 1996), respectively. Chan et al (1993) and others (Abbey et al, 1994;Layne et al, 1996;Lichtenstein et al, 1993, Valsta et al, 1996 have reported that when using alpha linolenic acid rich oils if the n-6an-3 ratio in the overall diet is high (namely b 5) an increase in plasma alpha linolenic acid can occur, but there is little, if any, increase in eicosapentaenoic acid content of plasma lipids above that of a standard reference diet. Increasing eicosapentaenoic acid levels by consuming alpha linolenic acid-rich oils appears to require a low n-6an-3 ratio (namely`3) in the overall diet as well as a high intake of alpha linolenic acid (Chan et al, 1993;Mantzioris et al, 1994Mantzioris et al, , 1995, not easily achieved by supplementing a low fat diet with walnuts, as in the present experiment.…”
Section: Discussionmentioning
confidence: 99%